### 3.136 $$\int x^{-1+n} (b+2 c x^n) (-a+b x^n+c x^{2 n})^p \, dx$$

Optimal. Leaf size=29 $\frac{\left (-a+b x^n+c x^{2 n}\right )^{p+1}}{n (p+1)}$

[Out]

(-a + b*x^n + c*x^(2*n))^(1 + p)/(n*(1 + p))

________________________________________________________________________________________

Rubi [A]  time = 0.0282607, antiderivative size = 29, normalized size of antiderivative = 1., number of steps used = 2, number of rules used = 2, integrand size = 32, $$\frac{\text{number of rules}}{\text{integrand size}}$$ = 0.062, Rules used = {1468, 629} $\frac{\left (-a+b x^n+c x^{2 n}\right )^{p+1}}{n (p+1)}$

Antiderivative was successfully veriﬁed.

[In]

Int[x^(-1 + n)*(b + 2*c*x^n)*(-a + b*x^n + c*x^(2*n))^p,x]

[Out]

(-a + b*x^n + c*x^(2*n))^(1 + p)/(n*(1 + p))

Rule 1468

Int[(x_)^(m_.)*((a_) + (c_.)*(x_)^(n2_.) + (b_.)*(x_)^(n_))^(p_.)*((d_) + (e_.)*(x_)^(n_))^(q_.), x_Symbol] :>
Dist[1/n, Subst[Int[(d + e*x)^q*(a + b*x + c*x^2)^p, x], x, x^n], x] /; FreeQ[{a, b, c, d, e, m, n, p, q}, x]
&& EqQ[n2, 2*n] && EqQ[Simplify[m - n + 1], 0]

Rule 629

Int[((d_) + (e_.)*(x_))*((a_.) + (b_.)*(x_) + (c_.)*(x_)^2)^(p_.), x_Symbol] :> Simp[(d*(a + b*x + c*x^2)^(p +
1))/(b*(p + 1)), x] /; FreeQ[{a, b, c, d, e, p}, x] && EqQ[2*c*d - b*e, 0] && NeQ[p, -1]

Rubi steps

\begin{align*} \int x^{-1+n} \left (b+2 c x^n\right ) \left (-a+b x^n+c x^{2 n}\right )^p \, dx &=\frac{\operatorname{Subst}\left (\int (b+2 c x) \left (-a+b x+c x^2\right )^p \, dx,x,x^n\right )}{n}\\ &=\frac{\left (-a+b x^n+c x^{2 n}\right )^{1+p}}{n (1+p)}\\ \end{align*}

Mathematica [A]  time = 0.0354757, size = 28, normalized size = 0.97 $\frac{\left (x^n \left (b+c x^n\right )-a\right )^{p+1}}{n (p+1)}$

Antiderivative was successfully veriﬁed.

[In]

Integrate[x^(-1 + n)*(b + 2*c*x^n)*(-a + b*x^n + c*x^(2*n))^p,x]

[Out]

(-a + x^n*(b + c*x^n))^(1 + p)/(n*(1 + p))

________________________________________________________________________________________

Maple [A]  time = 0.057, size = 45, normalized size = 1.6 \begin{align*} -{\frac{ \left ( -c \left ({x}^{n} \right ) ^{2}-b{x}^{n}+a \right ) \left ( -a+b{x}^{n}+c \left ({x}^{n} \right ) ^{2} \right ) ^{p}}{n \left ( 1+p \right ) }} \end{align*}

Veriﬁcation of antiderivative is not currently implemented for this CAS.

[In]

int(x^(-1+n)*(b+2*c*x^n)*(-a+b*x^n+c*x^(2*n))^p,x)

[Out]

-(-c*(x^n)^2-b*x^n+a)/n/(1+p)*(-a+b*x^n+c*(x^n)^2)^p

________________________________________________________________________________________

Maxima [A]  time = 1.25317, size = 58, normalized size = 2. \begin{align*} \frac{{\left (c x^{2 \, n} + b x^{n} - a\right )}{\left (c x^{2 \, n} + b x^{n} - a\right )}^{p}}{n{\left (p + 1\right )}} \end{align*}

Veriﬁcation of antiderivative is not currently implemented for this CAS.

[In]

integrate(x^(-1+n)*(b+2*c*x^n)*(-a+b*x^n+c*x^(2*n))^p,x, algorithm="maxima")

[Out]

(c*x^(2*n) + b*x^n - a)*(c*x^(2*n) + b*x^n - a)^p/(n*(p + 1))

________________________________________________________________________________________

Fricas [A]  time = 1.05441, size = 82, normalized size = 2.83 \begin{align*} \frac{{\left (c x^{2 \, n} + b x^{n} - a\right )}{\left (c x^{2 \, n} + b x^{n} - a\right )}^{p}}{n p + n} \end{align*}

Veriﬁcation of antiderivative is not currently implemented for this CAS.

[In]

integrate(x^(-1+n)*(b+2*c*x^n)*(-a+b*x^n+c*x^(2*n))^p,x, algorithm="fricas")

[Out]

(c*x^(2*n) + b*x^n - a)*(c*x^(2*n) + b*x^n - a)^p/(n*p + n)

________________________________________________________________________________________

Sympy [F(-1)]  time = 0., size = 0, normalized size = 0. \begin{align*} \text{Timed out} \end{align*}

Veriﬁcation of antiderivative is not currently implemented for this CAS.

[In]

integrate(x**(-1+n)*(b+2*c*x**n)*(-a+b*x**n+c*x**(2*n))**p,x)

[Out]

Timed out

________________________________________________________________________________________

Giac [A]  time = 1.18868, size = 39, normalized size = 1.34 \begin{align*} \frac{{\left (c x^{2 \, n} + b x^{n} - a\right )}^{p + 1}}{n{\left (p + 1\right )}} \end{align*}

Veriﬁcation of antiderivative is not currently implemented for this CAS.

[In]

integrate(x^(-1+n)*(b+2*c*x^n)*(-a+b*x^n+c*x^(2*n))^p,x, algorithm="giac")

[Out]

(c*x^(2*n) + b*x^n - a)^(p + 1)/(n*(p + 1))